Obstructive sleep apnea - risk factors, diagnosis and management - Marcelina Makuch; Marcin Makuch; Ewa Krzewicka-Romaniuk; Janusz Milanowski (Kazimierz Wielki University, 2020)
Obstructive sleep apnea (OSA) is a sleep-related breathing disorder that is characterised by obstructive apneas, hypopneas and respiratory effort-related arousals caused by repetitive collapse of the upper airway during sleep. Most pauses in breathing last between 10 and 30 seconds, but some may persist longer.